The ascent : a house can have many secrets - Hertmans, Stefan, 1951-; McKay, David, 1973- (New York : Pantheon Books, 2023)
"In this revealing and poignant story, Stefan Hertmans uncovers haunting details about the previous owner of his house and the crime he committed as a member of the Nazi police. In 1979 Stefan Hertmans became obsessed with a rundown townhouse in Ghent. The previous owners were mentioned only in passing during the acquisition, and it wasn't until the new millennium, long after he had sold the house, that he came across a memoir by the owner's son Adriaan Verhulst, a distinguished history professor and a former teacher of Hertmans', which revealed that his father was a former SS officer. Hertmans finds he is profoundly haunted by images of the family as ghostly presences in the rooms he had once known so well, he begins a journey of discovery-not to tell the story of Adriaan's father, but rather the story of the house and the people who lived in it and passed through it. Archives, interviews with relatives and personal documents help him imagine the world of this house as they reveal not only a marital drama, but also a connection between past visitors to the house and important figures in the culture and politics of Flanders now. A stunning and immersive reimagining of a family in a historical moment of great upheaval confirms Hertmans' always brilliant melding of fiction and nonfiction"--
Bevat afbeelding uit collectie Archief Gent op p. 358